Loop ileostomy or loop transverse colostomy for resectable rectal cancers - Çaparlar, Mehmet Ali; Dokçu, Şeref; Demirci, Salim (The European Research Journal, 2022)
Objectives: This retrospective study aimed to compare loop ileostomy (LI) with loop transverse colostomy (LTC) as covering stoma regarding the perioperative outcomes in patients who underwent low anterior resection for rectal cancer between 2015 and 2020. Methods: Data were collected from patient files and the hospital’s electronic database. The primary outcome measure was complications related to stoma formation, stoma reversal, and overall complications. Secondary outcome measures were hospital discharge time and readmission rate after discharge. Results: A total of 90 patients (38 female, 52 male; 56.6 ± 6.8 years) were included in the study. There were two groups considering the technique for covering stoma: Group LI (n = 50) and Group LTC (n = 40). Demographic and perioperative characteristics were similar. Primary outcome measure: Postoperative course was complicated in 49 (54.4%) patients. The complication rate was higher in the group LI than the group LTC (62% vs 45%; p = 0.03). Among them, 29 (59.2%) complications were related to the stoma formation related, and 14 (28.6 %) complications were related to the stoma reversal related, and 6 (12.2%) were overall complications. The rate of complications related to the stoma formation was higher in the group LI compared to the group LTC (20 [40%] vs. 9 [22.5%]; p = 0.01). The most common complication was periostomal skin irritation (48.3%) followed by dehydration (13.8%), stoma retraction (10.3%) patients, parastomal hernia (10.3%), bleeding (6.9%), anastomotic leak (3.4%), incisional hernia (3.4%), and high-output stoma (3.4%). Complications including incisional hernia, high output stoma, and anastomotic leakage (Grade C; requiring laparotomy) were observed only in the group LI. The morbidity rate in 30 days after the surgery was higher in the group LI compared to the group LTC (16 [32%] vs. 8 [20%]; p = 0.02). A total of 14 stoma reversal complications included incisional hernia in 7 (14.3%) patients, wound infection in 5 (10.2%) patients, and rectal bleeding in 2 (4.1%) patients. The rate of complications was not different between groups (16% vs. 15%; p = 0.41). Overall complications were similar between study groups (3 complications in each group; p = 0.73). Secondary outcome measure: The group LTC patients were discharged earlier compared to the group LI (7.1 ± 2.0 days vs. 9.4 ± 2.5 days; p = 0.03). The readmission rate after hospital discharge was higher in the LI group than the group LTC (18% vs. 12.5%; p = 0.02). Conclusions: It was concluded that LTC was superior compared to LI concerning complications after low anterior resection for rectum cancer.